Integrated Enzymatic Bioremediation: Efficient Decolorization of Textile DYE Effluents and Assessing Environmental Safety - Umamaheswari, K.; Sumathi, R.K. (UTTAR PRADESH JOURNAL OF ZOOLOGY, 2024)
Background: The synthetic dyes have become a staple in various industries, as colors play an important role in consumer choices. However, these dyes pose various health and environmental risks. Aim: The study aimed to identify bacterial isolates capable of producing enzymes for dye decolorization and assess their effectiveness in removing synthetic dyes. Additionally, the study sought to evaluate the toxicity levels of decolorized water samples, contributing to the development of eco-friendly dye removal technologies. Methodology: Bacterial isolates were obtained from textile effluent samples and screened for their ability to degrade synthetic dyes and produce enzymes. Enzyme production was evaluated through specific assays, and decolorization efficiency was determined using spectrophotometric analysis. Toxicity tests were conducted to assess the safety of the decolorized solutions. Furthermore potential isolate was subjected to 16sr RNA sequence analysis for species level identification. Results: The study isolated bacterial strains capable of producing lipase, amylase, cellulase, and laccase enzymes, with the majority of isolates (48%) exhibiting laccase production. One isolate, isolate 19 wasproducing laccase was demonstrated high decolorization efficiency for various synthetic dyes, comparable to the efficiency of enzyme producing isolates. Furthermore, the toxicity assay indicated that the decolorized solution using the laccase enzyme was non-toxic, while the isolate-treated solution showed toxicity. Additionally, potential isolate was identified as Achromobacter xylosoxidans with 16sr RNA sequence. Implications: The findings suggest that bacterial isolates have the potential to effectively decolorize synthetic dyes and produce non-toxic decolorized solutions. This research offers eco-friendly solutions for dye removal, addressing the need for sustainable water treatment and minimizing the environmental impact of dyeing processes.